Insurance Claims for Wrong-Side, Wrong-Organ, Wrong-Procedure, or Wrong-Person Surgical Errors: A Retrospective Study for 10 Years. Issue 1 (22nd January 2023) - Vacheron, Charles-Hervé; Acker, Amélie; Autran, Melanie; Fuz, Frederic; Piriou, Vincent; Friggeri, Arnaud; Theissen, Alexandre
Abstract : Objective: Serious adverse events, such as wrong-side, wrong-organ, wrong-procedure, or wrong-person errors, still occur despite the implementation of preventative measures. In France, we describe the claims related to such errors based on the database from one of the main insurance companies. Methods: A retrospective analysis of claims declared between January 2007 and December 2017 to Relyens, a medical liability insurance company (Sham), was performed. Their database was queried using the following keywords: "wrong side, " "wrong organ, " and "wrong person." Results: We collected 219 claims (0.4% of the total claims). The main specialties involved were orthopedics (34% of cases), neurosurgery (14%), and dentistry (14%). The claims were related to wrong organ (44%), side (39%), identity (13%), or procedure (4%). Juridical entity involved were mainly public facility (69%), followed by private facility (19%) or private physician (10%). The mean number of annual claims made has decreased of 20% since the mandatory implementation of the checklist in 2010 (22 versus 17.5 events per year). The main risk factors identified according to the ALARM protocol were factor related to the team (87%) or to the task to accomplish (78%). A direct causal factor was involved in 20% of the files, the main one being the organization (43%) closely related to the medical file (36%). The settlement was performed by conciliation in 69% of the claim and in court in 30%. The compensation was higher during a court settlement. Conclusions: Wrong-side, wrong-organ, wrong-procedure, or wrong-person surgical errors are rare but fully preventable by the implementation of a safety culture.